2020
DOI: 10.1002/gps.5291
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index, residual psychotic symptoms, and inflammation associated with brain volume reduction in older patients with schizophrenia

Abstract: ObjectiveObesity, aging, and pathophysiology of schizophrenia (SCZ) may collectively contribute to the gray matter loss in brain regions of SCZ. We attempted to examine the association between volumes of specific brain regions, body mass index (BMI), inflammatory markers, and clinical features in older SCZ patients.MethodClinically stable outpatients with schizophrenia (DSM‐IV) aged ≥50 years were recruited to undergo whole‐brain magnetic resonance imaging. We measured patients' plasma levels of soluble tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…These included anterior cingulate, temporal pole, and key parts of frontal lobe, that is areas which are considered integral to neuroanatomy of major psychiatric disorders. This is in keeping with previous studies which also demonstrated additive effects of obesity and psychiatric disorders on brain structure [ 20 , 23 , 25 , 26 , 32 ]. We would expect changes in the regions associated with both conditions to be inflated in studies which did not control for BMI.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These included anterior cingulate, temporal pole, and key parts of frontal lobe, that is areas which are considered integral to neuroanatomy of major psychiatric disorders. This is in keeping with previous studies which also demonstrated additive effects of obesity and psychiatric disorders on brain structure [ 20 , 23 , 25 , 26 , 32 ]. We would expect changes in the regions associated with both conditions to be inflated in studies which did not control for BMI.…”
Section: Discussionsupporting
confidence: 93%
“…With 3021 individuals, this is the largest study investigating associations between schizophrenia, BMI and brain structure, and one of only 2 such studies [ 25 , 26 ]. We benefited from the significant methodological refinements and harmonization in the ENIGMA study and from access to a highly generalizable, multi-site sample of individuals with schizophrenia from around the world, thus representing a broad spectrum of individuals with this disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Janney et al also pointed out that there was no association between obesity and PANSS psychiatric symptoms 45 . However, other studies have shown the opposite conclusion that obesity was a risk factor for cognitive impairment or rich psychiatric symptoms in schizophrenia [46][47][48][49][50] . Therefore, the relationship between obesity and cognitive and mental symptoms needs to be further studied.…”
Section: Discussionmentioning
confidence: 94%
“…One study (48) found elevated levels of osteoprotegerin-a tumor necrosis factor receptor-associated with smaller total hippocampal volume, though no correlations with other cytokines, including TNF-α, nor IL-6, were found in the same study. Kudo et al (50) observed negative association between sTNF-R2 and hippocampal volume while Tsai et al (53) found sTNF-R1 was positively associated with right amygdala volume. Bossù et al reported an association between lower levels of pro-inflammatory cytokine IL-18 and smaller hippocampal volumes (44).…”
Section: Association Between Inflammatory and Neuroimaging Markersmentioning
confidence: 99%